2021
DOI: 10.3788/col202119.090601
|View full text |Cite
|
Sign up to set email alerts
|

Compact vector twist sensor using a small period long period fiber grating inscribed with femtosecond laser

Abstract: We propose and demonstrate a sensitive vector twist sensor based on a small period long period fiber grating (SP-LPFG) fabricated with femtosecond laser. The fabricated SP-LPFG is compact in size (2.8 mm), and shows strong polarization dependent peaks in its transmission spectrum due to the vectorial behavior of high order cladding modes. Twist sensing is realized by monitoring the polarization dependent peaks, since the polarization of input light changes with fiber twist. The proposed sensor can be interroga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…In addition, many technologies are borrowed from speech recognition technology and are also used to judge the motion state of the human body [18]. In terms of human motion gesture recognition, some basic actions of people's daily life, such as walking, jogging, sitting, and standing, can also be successfully recognized [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, many technologies are borrowed from speech recognition technology and are also used to judge the motion state of the human body [18]. In terms of human motion gesture recognition, some basic actions of people's daily life, such as walking, jogging, sitting, and standing, can also be successfully recognized [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although long-period grating has high mechanical strength, the limitations of its structure and sensing principle result in low torsional sensing sensitivity. 6 Researchers have found that introducing helical structures into optical fibers can benefit sensors in identifying torsion direction and improving sensitivity. 7 However, the production of helical structures often requires expensive motors and precise control platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber twisting is a simple and versatile method of modification of fiber structure, which provides additional opportunities for controlling light propagation. Twisted fibers can be used in different applications of fiber optics-in particular, in sensors of current [1], torsion [2,3], temperature [4] in fiber lasers [5], circular polarizers, couplers [6], optical vortices generators [7][8][9], and converters [10]. The optical effects of twisting are also of great fundamental interest [11], especially in relation with orbital angular momentum studies and vortex beams [12].…”
Section: Introductionmentioning
confidence: 99%